PixGuard-Sim: A Deadline-Aware Testbed for Pix Fraud Detectors - Kapelinski, Cristhian; Kreutz, Diego (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
Brazilian regulation gives a paying institution about a second and a half to decide whether a suspect Pix transfer should be diverted for review before it settles, on a system used by 170 million people where settlement is irreversible. Yet every openly released payment-fraud dataset and baseline we surveyed is scored in batch, with no reference to that window. PixGuard-Sim is an open testbed that scores a detector against the window from the latency it measures, and releases a Pix-native generator with a settlement clock and two scenarios open data omits: multi-hop MED-2.0 refund tracing and payment under coercion. Scoring accuracy and timing together pulls them apart. The most accurate detectors we evaluate are cloud reasoning models that never saw a labeled event from this stream: the stronger finds 112 of 150 frauds where a random forest fitted to the data finds 93, and neither answers in time. Ranking by accuracy alone selects what cannot be deployed.